2016
DOI: 10.1590/1678-775720150583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the remineralization capacity of CPP-ACP containing fluoride varnish by different quantitative methods

Abstract: Objective The aim of this study was to evaluate the efficacy of CPP-ACP containing fluoride varnish for remineralizing white spot lesions (WSLs) with four different quantitative methods.Material and Methods Four windows (3x3 mm) were created on the enamel surfaces of bovine incisor teeth. A control window was covered with nail varnish, and WSLs were created on the other windows (after demineralization, first week and fourth week) in acidified gel system. The test material (MI Varnish) was applied on the demine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
(51 reference statements)
6
20
0
1
Order By: Relevance
“…Nowadays, dental caries management is based on conservative and preventive approaches. 24 Different materials and methods are currently being evaluated to achieve newer approaches for the remineralization of demineralized dentin that will aid in treating dentin caries and dentin hypersensitivity. 25 Previous reports have shown a major role of many commercially available products in enhancement of dental remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, dental caries management is based on conservative and preventive approaches. 24 Different materials and methods are currently being evaluated to achieve newer approaches for the remineralization of demineralized dentin that will aid in treating dentin caries and dentin hypersensitivity. 25 Previous reports have shown a major role of many commercially available products in enhancement of dental remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Majithia et al, (30) observed that varnish with CPP ACP with uoride (MI Varnish) had better results in remineralization when compared to the other materials.Cochrane et al, (31) observed a fast discharge of calcium and inorganic phosphate particles under neutral condition which is reliable with the bioavailable nature of CPP ACP contained within the varnish and that was related to high water solubility of CPP-ACP. Savas et al, (32) recommended the use of CPP ACP containing uoride varnish (MI Varnish) in the dental clinics as it improves the remineralization of incipient carious lesions after a single application. On the other hand, multiple remineralization researches done by Karabekiroglu et al, (33) and Robertson et al, (34) stated that the e ciency of casein phosphopeptide amorphus calcium phosphate is unreliable in reducing the white spot lesions.…”
Section: Discussionmentioning
confidence: 99%
“…From the photograph, the computer software was used Health lesion is reduced by diffuse reflection, which is defined as F2 (Figure 4). The software calculates the difference between F1 and F2 (∆F = F2 − F1) and the dimension where the reduced fluorescence was observed (S), and then determines mineral loss by multiplying ∆F by S (∆Q) [14] [15]. Since ∆F is a negative value, ∆Q is also negative.…”
Section: Qlf-dmentioning
confidence: 99%